Effects of Thermomechanical Couplimg Op the Stress State During Incremental Loading - Niezgoda, T. (Engineering Transactions, 1992)
In the paper ah FEM algorithm for solving coupled thermoplasticity problems is presented. Theoretical considerations arc followed by a numerical example in which the influence of the temperature field coupled with the plastic deformation field on the stress state is studied.